Data supporting: 'CO2 absorption into aqueous ammonia using membrane contactors: Role of solvent chemistry and pore size on solids formation for low energy solvent regeneration' - Bavarella, Salvatore; Luqmani, Benjamin A.; Thomas, Navya; Brookes, Adam; Moore, Andrew; Vale, Peter C. J.; Pidou, Marc; McAdam, Ewan (Cranfield University, 2022)
Solids formation can substantially reduce the energy penalty for ammonia solvent regeneration in carbon capture and storage (CCS), but has been demonstrated in the literature to be difficult to control. This study examines the use of hollow fibre membrane contactors, as this indirect contact mediated between liquid and gas phases in this geometry could improve the regulation of solids formation. Adoption of a narrower pore size membrane was shown to dissipate wetting after crystallisation in the solvent, illustrating membrane contactors as a stable platform for the sustained separation of CO2 coupled with its simultaneous transformation into a solid. Through resolving previous challenges experienced with solids formation in multiple reactor configurations, the cost benefit of using ammonia as a solvent can be realised, which is critical to enabling economically viable CCS for the transition to net zero, and can be exploited within hollow fibre membrane contactors, eliciting considerable process intensification over existing reactor designs for CCS.
Keywords: precipitation'; 'carbon capture and storage (CCS)'; 'membrane crystallisation'; 'ammonium bicarbonate solid formation'; 'heterogeneous nucleation'